Minimally invasive caries detection with fiber optic transillumination: Deteksi karies minimal invasif dengan fiber optic transillumination - Putu Maya Rizkita Putri; Nurhayaty Natsir (Makassar Dental Journal PDGI Makassar, 2026)
Failure to detect caries early affects the effectiveness of preventive care by dentists. Early detection of caries helps dentists prepare and determine the appro-priate and accurate type of treatment based on caries risk, lesion severity, surface integrity and caries activity, in relation to the need for or absence of treat-ment without instrumentation on non-cavity lesions. Successful early detection of caries helps dentists prevent and restore teeth before more extensive da-mage occurs. Caries is one of the dental and oral health problems that needs attention. The process of caries begins with the formation of white spot lesions, which, if treated quickly, will prevent extensive damage to the tooth structure, so early detection of caries is necessary to determine the location and extent of caries. Fibre optic transillumination is a minimally invasive method that can be used to detect caries through light transmission without invasive instruments to determine the treatment plan. It is concluded that the effectiveness of caries prevention treatment can be achieved through early detection of caries. Fibre optic transillumination is a minimally invasive method for detecting caries through light transmission.